Effectiveness of the Puspaga (Family Learning Center) Program in Preventing Early Marriage in Pekanbaru City - Andini Puspita Martha; Febri Yuliani (CV. Rayyan Dwi Bharata, 2024)
The problem in this research is early marriage which continues to occur in Pekanbaru City and is a national issue currently facing Indonesia. Early marriage is a serious problem because it violates children's rights. One of the regional government's efforts to prevent early marriage is through the flagship program of the Ministry of Women's Empowerment and Child Protection (PPPA) known as the Family Learning Center (Puspaga). The Family Learning Center (Puspaga) plays an important role in efforts to prevent early marriage by providing knowledge and professional guidance to help protect children's rights. How effective is the Puspaga (Family Learning Center) program in preventing early marriage in Pekanbaru City. The aim is to analyze and describe the effectiveness of policies and identify actions that need to be followed up using Campbell's theory in Mutiarin (2021) which is seen from indicators of program success, target success, satisfaction with the program, level of input and output, and achievement of overall goals. This research uses descriptive qualitative methods. The results of this research show that the program has been quite successful with the socialization and services that continue to be provided. The success of the target has not been achieved because many people do not know Puspaga. Satisfaction with the program has not been felt by many people. Input and output levels can be said to be effective because they have good human resource input and service output provided. Achievement of overall goals has not yet been achieved. Actions that need to be followed up are increasing human resources, providing scheduled outreach and cross-sectoral collaboration.